2020
DOI: 10.1101/2020.02.19.956946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for the recognition of the 2019-nCoV by human ACE2

Abstract: Angiotensin-converting enzyme 2 (ACE2) has been suggested to be the cellular receptor for the new coronavirus (2019-nCoV) that is causing the coronavirus disease 2019 . Like other coronaviruses such as the SARS-CoV, the 2019-nCoV uses the receptor binding domain (RBD) of the surface spike glycoprotein (S protein) to engage ACE2. We most recently determined the structure of the full-length human ACE2 in complex with a neutral amino acid transporter B 0 AT1. Here we report the cryo-EM structure of the full-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 7 publications
(9 reference statements)
0
92
0
2
Order By: Relevance
“…The structure of protein complex between RBD region of S protein of SARS-CoV and human ACE2 has been resolved (PDB: 2AJF) [7]. Recently, the structure of SARS-CoV-2 RBD with human ACE2 was also determined [16,17]. We used Chimera software to display homologous model, and obtained the interaction complex structure of RBD region of SARSr-CoV (SARS-CoV-2 and SARS-CoV) and cat/dog/pangolin/Chinese hamster ACE2.…”
Section: Structure Simulation Of the Protein Complex Of Sarsr-cov Rbdmentioning
confidence: 99%
“…The structure of protein complex between RBD region of S protein of SARS-CoV and human ACE2 has been resolved (PDB: 2AJF) [7]. Recently, the structure of SARS-CoV-2 RBD with human ACE2 was also determined [16,17]. We used Chimera software to display homologous model, and obtained the interaction complex structure of RBD region of SARSr-CoV (SARS-CoV-2 and SARS-CoV) and cat/dog/pangolin/Chinese hamster ACE2.…”
Section: Structure Simulation Of the Protein Complex Of Sarsr-cov Rbdmentioning
confidence: 99%
“…Research has confirmed that SARS-CoV-2 infects host cells by binding to angiotensin converting enzyme II (ACE2), [10][11][12] and ACE2 is highly expressed in nasopharyngeal cells. 13 More importantly, current research detected a high viral load in the nasopharynx soon after symptom onset.…”
Section: (Which Was Not Peer-reviewed)mentioning
confidence: 99%
“…It has been proved that SARS-CoV-2 uses ACE2 as a viral receptor for entry process [2] . ACE2 mRNA is highly expressed and stabilized by B 0 AT1 in gastrointestinal system [3,4], providing a prerequisite for SARS-CoV-2 infection. To further investigate the clinical significance of SARS-CoV-2 RNA in feces, we examined the viral RNA in feces from 71 patients with SARS-CoV-2 infection during their hospitalization.…”
mentioning
confidence: 99%